The Role of Financial Literacy in Household Finance Decision-Making - Goso Goso; Syamsu Alam; Muhammad Yunus Amar; Musran Munizu (JURNAL EKBIS, 2022)
The purpose of this study is to investigate how the importance of financial literacy is connected to a husband and wife's knowledge, abilities, and views, as well as their agreement in making decisions concerning life insurance participation. Married couples do separate in-depth interviews, with wives conducting separate interviews and husbands conducting joint interviews. The major topic we cover is how to do cognitive mapping on data received from interviews with people of different nationalities and cultures. Despite having low levels of financial literacy (financial knowledge and abilities), certain married couples play a more important role in household financial decision-making. This study project will have an impact on how financial information is perceived and how money and consumption are distributed.